Do Monetary Policy Instruments Influence Capital Market Returns in Nigeria? - Ogbonna, Udochukwu Godfrey; Ejem, Chukwu Agwu (American Finance & Banking Review, 2020)
This study concisely examined the relationship between monetary policy variables and performance of the Nigerian Capital Market, analyzed with appropriate econometric tools. After the analysis, the outputs revealed the following; the entire monetary policy variables employed only monetary policy rate has significant relationship with the performance of the capital market in Nigeria. It was also found that the previous information about the all share index has the capacity to predict future returns in capital market in Nigeria. On this note, the researchers are of the opinion to embark on prompt disclosure of the daily all share indexes by regulatory authorities, thereby refurbishing the efficiency of the Nigeria Capital Market. It is also suggested to adopt alternative means of disclosure apart from the national television stations and national daily newspapers because of our technological know-how in Nigeria.